Strategi Penghimpunan Dana dalam Program Palembang Sehat di Baznas Kota Palembang - Ayu Kurniasih; Achmad Syarifudin; Anang Walian (CV. ITTC INDONESIA, 2026)
This study aims to examine the fundraising strategy implemented in the Palembang Sehat Program at BAZNAS Palembang City and to identify the supporting and inhibiting factors affecting its implementation. This research employed a qualitative approach using a descriptive method. Data were collected through interviews, observations, and documentation, and were analyzed using data reduction, data presentation, and conclusion drawing. Henry Mintzberg's strategy theory was used as the analytical framework to examine the fundraising strategies implemented by BAZNAS Palembang City. The findings reveal that the fundraising strategy for the Palembang Sehat Program is carried out through systematic planning, strengthening the network of Zakat Collection Units (UPZ), conducting public outreach, establishing institutional partnerships, and utilizing digital media as a communication platform. The primary strategy emphasizes persuasive and educational communication by highlighting the benefits of the Palembang Sehat Program for underprivileged communities while optimizing religious occasions, such as Ramadan and Islamic holidays, to maximize fundraising efforts. The supporting factors include a high level of public trust in BAZNAS, supportive government regulations, and strong public awareness of health-related social programs. Meanwhile, the inhibiting factors include unstable fundraising due to dependence on specific periods, limited human resources in reaching potential donors, and the tendency of some people to distribute donations directly to beneficiaries rather than through zakat institutions. The study concludes that the fundraising strategy implemented by BAZNAS Palembang City has been effectively carried out. However, further optimization of communication strategies, stronger institutional partnerships, and enhanced human resource capacity are needed to ensure sustainable fundraising and improve the effectiveness of the Palembang Sehat Program.